Digitization in health-related self-help – Results of an online survey among self-help organizations in Germany. (August 2022) - Nickel, Stefan; Bremer, Katharina; Dierks, Marie-Luise; Haack, Marius; Wittmar, Silke; Borgetto, Bernhard; Kofahl, Christopher
Background: Nowadays, much hope and expectations are associated with digitization in the health sector. The digital change also affects health-related self-help. A nationwide survey of self-help organizations (SHOs) aimed to show chances and limitations in the use of interactive IT tools like webforums, online meetings or social media as well as digital infrastructures for their organizational management. In this survey, we also determined whether SHO staff themselves have support and qualification needs with regard to this topic. Design: The online survey was conducted between 14 November and 8 December 2019, i.e., immediately before the outbreak of the Covid-19 pandemic. The questionnaire consisted of 50 questions consisting of 180 single items which could be answered in 30–40 min. After two reminder letters, 119 questionnaires of the SHOs were gathered and analysed. Results: SHOs already have a lot of experience with digital media/tools (e.g., own homepage, social media, cloud computing). Some tools are attested a "high" or "very high" benefit by more than 80% of users. Perceived benefits, however, are also facing a number of problems, ranging from lack of resources to data protection issues. Despite, or even because of the limits of digitization, there is great desire and need for support and further training in SHOs (and self-help groups). Conclusions: At many points in the survey it was shown that digital media can be a useful extension of "traditional" collective self-help. Taking into account the risks and limitations associated with digital tools, SHOs can be central stakeholders in digitization in health-related self-help. Patient or Public Contribution: The study was financially supported by the Federal Ministry of Health, Germany. A detailed representation of the results is publicly available at:https://www.uke.de/dish .